Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
(- 3, 1 )
Step-by-step explanation:
2x - 2y = - 8 → (1)
x + 2y = - 1 → (2)
adding the 2 equations term by term will eliminate y
3x + 0 = - 9
3x = - 9 ( divide both sides by 3 )
x = - 3
substitute x = - 3 into either of the 2 equations and solve for y
substituting into (2)
- 3 + 2y = - 1 ( add 3 to both sides )
2y = 2 ( divide both sides by 2 )
y = 1
solution is (- 3, 1 )
Answer:
(–3, 1)
Step-by-step explanation:
Step 1: Solve for x
2x – 2y = –8 -----------(1)
x + 2y = –1. -------------(2)
- Add equation 1 to 2
⇒2x + x| -2y + 2y |= -8 -1
⇒3x = -9
- Divide both side by the coefficient of x
⇒3x/3 = -9/3
⇒x = -3
Step 2; Solve for y
- Substitute into equation 2
x + 2y = –1
(-3) + 2y = -1
- Add 3 from both sides
-3 + 2y + 3 = -1 + 3
2y = 2
- divide both side by two
2y/2 = 2/2
y = 1
So, ( x,y) ⇒(-3,1)
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.